Comparison of the efficacy of dexmedetomidine and dexmedetomidine-magnesium combination in sedation management in intensive care (Annals of Medical Research, 2025)
Aim: The aim of this study was  to evaluate the correlation  of sedation with subjective clinical sedation scores and compare plasma cortisol levels as an objective marker between two groups: patients sedated with dexmedetomidine alone and patients sedated with a combination  of dexmedetomidine and magnesium via mechanical ventilation.Materials and Methods: A total of 50 patients were enrolled and divided into two groups. Group 1 (dexmedetomidine group) received a loading dose 1μg/kg, followed by a continuous infusion  0.2-1.4 μg/kg/hour for 24 hours. Group 2 (dexmedetomidine+magnesium group) received a loading dose  1 μg/kg of dexmedetomidine, followed by a continuous infusion  0.2-1.4 μg/kg/hour for 24 hours, along with two bolus doses of 2 grams of magnesium and a continuous infusion of 16mg/24 hours. Sedation scale scores, Glasgow coma scores, heart rate, and plasma cortisol levels at baseline and at 24 hours were recorded throughout the 24-hour study period.Results: On the 24th hour, cortisol levels were significantly lower in Group 2 (p
Keywords: Intensive care; Sedation; Dexmedetomidine; Magnesium; Cortisol